Associations of Academic Performance and Physical Fitness in Zaragoza´s adolescent students - Castro López, R.; Pérez Gómez, V.; Cachón Zagalaz, J.; Zagalaz Sánchez, Mª L. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
Introduction: The aim of this study is to analyze the relationship between fitness and academic achievement based on variables such as gender, course and nationality. Methods: 338 students were analyzed. Academic achievement was based on academic average, scores and average on mathematics and language and academic suspension. Fitness was evaluated with the EUROFIT Battery. The level of statistical significance was p<0.05. Results: Significant results were observed in the total sample between fitness and academic performance (p<.01). Flexibility test was significantly associated with academic achievement (all academic variables p <.01), In terms of gender, significant relationships appear in both. Depending on the course, significant relationships exist in the first courses. In terms of origin, native students present significant association but this association is punctual in foreign students. Conclusions: This study shows a significant relationship between fitness and academic performance, depending on items and different characteristics presents in the study.